A primary esophageal MALT lymphoma patient with Helicobacter pylori infection achieved complete remission after H. pylori eradication without anti-lymphoma treatment. (2017) - Moriya, Keiichi; Tamura, Hideto; Nakamura, Kyoko; Hosone, Masaru; Inokuchi, Koiti
Abstract: Primary esophageal lymphoma is an extremely rare disease. We report a 76-year-old woman with esophageal lymphoma who achieved remission after Helicobacter pylori (HP) eradication. Esophagogastroduodenoscopy (EGD) revealed a mass in the lower esophagus, and she was diagnosed with stage IE mucosa-associated lymphoid tissue (MALT) lymphoma. She rejected any anti-lymphoma treatment except for HP eradication. Follow-up EGD demonstrated the disappearance of the esophageal MALT lymphoma 2 months after HP eradication, and she remained in remission for more than 3 years. Our results demonstrate that HP eradication may be effective as initial therapy in primary esophageal MALT lymphoma patients with HP infection.